2016
DOI: 10.1158/1078-0432.ccr-15-0459
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative versus Non–Triple-Negative Breast Cancers in High-Risk Women: Phenotype Features and Survival from the HIBCRIT-1 MRI-Including Screening Study

Abstract: Purpose: To compare phenotype features and survival of triple-negative breast cancers (TNBC) versus non-TNBCs detected during a multimodal annual screening of high-risk women.Experimental Design: Analysis of data from asymptomatic high-risk women diagnosed with invasive breast cancer during the HIBCRIT-1 study with median 9.7-year follow-up.Results: Of 501 enrolled women with BRCA1/2 mutation or strong family history (SFH), 44 were diagnosed with invasive breast cancers: 20 BRCA1 (45%), 9 BRCA2 (21%), 15 SFH (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 46 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Still, Moller et al report a 10‐year survival of only 69% for BRCA1 mutation carriers participating in an MRI‐based screening program, which points to the still much worse outcome in this specific population . Podo et al, however, showed that the 5‐year overall survival difference between triple‐negative breast cancers and less aggressive subtypes was relatively small (86% ± 9% for TNBCs vs. 93% ± 5% for others) in patients who participated in the HIBCRIT‐1 trial …”
Section: Outcome Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, Moller et al report a 10‐year survival of only 69% for BRCA1 mutation carriers participating in an MRI‐based screening program, which points to the still much worse outcome in this specific population . Podo et al, however, showed that the 5‐year overall survival difference between triple‐negative breast cancers and less aggressive subtypes was relatively small (86% ± 9% for TNBCs vs. 93% ± 5% for others) in patients who participated in the HIBCRIT‐1 trial …”
Section: Outcome Effectsmentioning
confidence: 99%
“…53 Podo et al, however, showed that the 5-year overall survival difference between triple-negative breast cancers and less aggressive subtypes was relatively small (86% AE 9% for TNBCs vs. 93% AE 5% for others) in patients who participated in the HIBCRIT-1 trial. 54…”
Section: Outcome Effectsmentioning
confidence: 99%
“…As a consequence, TNBC patients do not benefit from modern receptor‐targeted therapies . Moreover, TNBC patients have a significantly higher risk of recurrence and death than patients with other types of breast cancer . Disease heterogeneity has limited the development of molecularly targeted therapeutics .…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, TNBC patients have a significantly higher risk of recurrence and death than patients with other types of breast cancer. 2 Disease heterogeneity has limited the development of molecularly targeted therapeutics. 3 The current standard of care for TNBC involves surgical resection of the primary tumor preceded or followed by ionizing radiation and a cocktail of chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was further developed as bilateral highly spatially resolved contrast-enhanced (CE) dynamic study, which is now currently considered superior for breast cancer (BC) detection to any other imaging technique with a reported pooled sensitivity and specificity of 93.2 and 71.1%, respectively (2), as also shown by studies on MRI screening of women at increased risk of BC (36). In fact, CE-MRI provides a physiopathological information that correlates with increased vascularity, vascular permeability, and interstitial space in malignant tissue, not available from mammography and ultrasound.…”
Section: Introductionmentioning
confidence: 99%